2014
DOI: 10.1136/bmjopen-2014-006156
|View full text |Cite
|
Sign up to set email alerts
|

The Improving Rural Cancer Outcomes (IRCO) Trial: a factorial cluster-randomised controlled trial of a complex intervention to reduce time to diagnosis in rural patients with cancer in Western Australia: a study protocol

Abstract: IntroductionWhile overall survival for most common cancers in Australia is improving, the rural–urban differential has been widening, with significant excess deaths due to lung, colorectal, breast and prostate cancer in regional Australia. Internationally a major focus on understanding variations in cancer outcomes has been later presentation to healthcare and later diagnosis. Approaches to reducing time to diagnosis of symptomatic cancer include public symptom awareness campaigns and interventions in primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…It is well known that geographic distance from urban advanced care centers has a negative impact on cancer survival, leading to limited access to appropriate screening, later stages at diagnosis, and worse overall survival. 3,21,2729 Multiple Australian studies have demonstrated that lung cancer patients who live further from specialist hospitals with thoracic surgeons on staff have higher cancer related mortality rates. 4,15 This is likely due to the fact that patients admitted to specialist hospitals were more likely to receive a resection, which was similarly associated with improved survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that geographic distance from urban advanced care centers has a negative impact on cancer survival, leading to limited access to appropriate screening, later stages at diagnosis, and worse overall survival. 3,21,2729 Multiple Australian studies have demonstrated that lung cancer patients who live further from specialist hospitals with thoracic surgeons on staff have higher cancer related mortality rates. 4,15 This is likely due to the fact that patients admitted to specialist hospitals were more likely to receive a resection, which was similarly associated with improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Survival outcomes are reduced in patients from rural environments, often due to delays in diagnosis, treatment, and follow up as well as unavailability of advanced care including multimodality treatment options and enrollment in clinical trials. 36 Systemic therapy is the primary method of treatment in these patients with local or distant metastatic disease, and when combined with appropriate surgical resection can lead to significantly improved survival rates. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Intervention studies directed at trying to educate people about lung cancer signs and symptoms (Emery et al, 2014;Smith et al, 2013) are very recent. System level interventions seeking to improve diagnostic processes include policy change such as the UK's 2-week-wait referral pathway (Neal et al, 2014) …”
Section: Timely Diagnosis and Referralmentioning
confidence: 99%
“…65,66 Whether raising awareness of individual symptoms, or symptom combinations, of other less common cancers will also promote more timely help-seeking currently remains unclear. 5 Cancer h literacy strongly associated with disadvantaged socio-economic and ethnic minority groups. 67 Linking information on awareness with other healthcare activities awareness: data from a trial that involved offering information about symptoms of breast cancer to women attending breast screening revealed an increase in the proportion of women who were breast cancer aware from 6%, to 21% (OR 8.1, 95% CI 2.7 25) when assessed two years later using a validated questionnaire.…”
Section: [H2] Symptom Awareness Campaignsmentioning
confidence: 99%
“…promoting earlier presentation of potential cancer symptoms [3][4][5][6][7] ; the use of new technologies in the assessment of pigmented skin lesions 8 ; the use of computerized decision-support tools in the diagnosis of cancer in primary care 9 ; cancer-specific education for general practitioners (GPs) 5,10 ; direct access to low-dose CT for the early detection of lung cancer in primary care 11 ; and lower symptom thresholds for urgent use of chest radiography 12 . Thus far, no trial has included a sufficiently large cohort to address the issue of whether or not expedited cancer diagnosis in primary care is beneficial, in terms of either mortality or morbidity.…”
Section: [H1] Benefits Of Expedited Symptomatic Diagnosis [H2] Types mentioning
confidence: 99%